PENGGUNAAN MEDIA PAPAN TEMPEL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI 1 ANDEUE - Junaidah; Nurul Alam Naqiatuddin (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2024)
This study aims to determine the use of clipboard media to improve learning outcomes in 4th grade students of SD Negeri 1 Andeue. The research design used is Classroom Action Research (CAR) which is carried out in three cycles. Data collection techniques in this study are observation, tests and documentation. The results of the average value obtained by students in cycle I were 63.86 with a percentage of completion of 40.90%. In cycle II, the average value obtained by students was 77.27 with a percentage of completion of 72.72% and in cycle III there was an increase with an average value obtained by students of 87.95 with a percentage of completion of 90.90%. So, it can be concluded that the use of clipboard media can improve the learning outcomes of 4th grade students of SD Negeri 1 Andeue.